Homer in the twentieth century between world literature and the Western canon - Graziosi, Barbara; Greenwood, Emily (Classical presences, 2010)
Exploring the crucial place of Homer in the cultural landscape of the 20th century, these essays contributes to debates about the nature of the Western literary canon, the evolving notion of world literature, the relationship between orality and the written word, and the dialogue between texts across time and space.